Sensors data encryption using TSFS Algorithm - Shatha Habeeb; Rehab F. Hassan (Journal of Madenat Alelem University College, 2018)
Sensors data security has an increasing importance with the use of sensors in all kinds of real world applications, after being collected from sensors, huge amount of data will be stored in a database, with different types of analysis. It should be protected from all attack kinds considering sensor data as sensitive data. Several security algorithms are implemented to present database protection, and to have powerful protection, the sensitive data should be covered from the risk of being attacked and not stored as original text only, therefore, the key solution for protecting database is to encrypt it. This paper provides database encryption for data acquisition from sensor. TSFS (Transposition, Substitution, Folding, and Shifting) algorithm has been used with three strong and different keys matrices after two sub-steps for key generation using genetic algorithm and expansion by column shifting. By implementing the enhanced algorithm, an efficient and strong database security system has been achieved to data received from sensor.